Heterologous fibrin sealant derived from snake venom: From bench to bedside - an overview - Ferreira, Rui Seabra [UNESP]; de Barros, Luciana Curtolo [UNESP]; Abbade, Luciana Patrícia Fernandes [UNESP]; Barraviera, Silvia Regina Catharino Sartori [UNESP]; Silvares, Maria Regina Cavariani [UNESP]; de Pontes, Leticia Gomes [UNESP]; dos Santos, Lucilene Delazari [UNESP]; Barraviera, Benedito [UNESP] (Springer Nature, 2017)
Hemostatic and adhesive agents date back to World War II, when homologous fibrin sealant came onto scene. Considering that infectious diseases can be transmitted via human blood, a new heterologous fibrin sealant was standardized in the 1990s. Its components were a serine protease (a thrombin-like enzyme) extracted from the venom of Crotalus durissus terrificus snakes and a fibrinogen-rich cryoprecipitate extracted from the blood of Bubalus bubalis buffaloes. This new bioproduct has been used as a coagulant, sealant, adhesive and recently as a candidate scaffold for mesenchymal stem cells and bone and cartilage repair. This review discusses the composition of a new heterologous fibrin sealant, and cites published articles related to its preclinical applications aiming at repairing nervous system traumas and regenerating bone marrow. Finally, we present an innovative safety trial I/II that found the product to be a safe and clinically promising candidate for treating chronic venous ulcers. A multicenter clinical trial, phase II/III, with a larger number of participants will be performed to prove the efficacy of an innovative biopharmaceutical product derived from animal venom.
Keywords: Buffaloes; Cryoprecipitate coagulum; Fibrin sealant; Snake venom; Thrombin-like enzyme